Medicina rigenerativa in ortopedia e traumatologia: la stimolazione biofisica - D'Addona, A.; Izzo, A.; Ruosi, L.; Santulli, A.; Ruosi, C. (Lo Scalpello - Journal, 2019)
REGENERATIVE MEDICINE IN ORTHOPAEDICS: THE BIOPHYSICAL STIMULATIONCartilage lesions are considered to be the first cause of disability in the active population. Treating cartilage injuries isoften a challenge for orthopaedic surgeons, owing to the poor regenerative potential of chondrocytes. Pulsedelectromagnetic fields (PEMFs) improve cellular proliferation and migration, and ECM induction. PEMFs during orafter surgery for chondral lesion have been demonstrated to be useful in inducing better repair andmigration ofchondrocytes into the bioscaffolds, and to lead to improvement in patient symptoms after surgery. In this review of theliterature, we collected a significative number of studies, which support using biophysical stimulation, in particularPEMFs, as first-line treatment during and after surgery to treat chondral lesion.